Concepts of justice in the degrowth debate - Sonja Hennen (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
Degrowth's search for a qualitatively and quantitively different economy is given legitimacy by the severity of the socio-ecological crisis, paired with a lack of evidence that resource use and environmental impact can be decoupled in absolute terms at a meaningful point in time and studies refuting the trickle-down hypothesis. However, there are few accounts of the potentially adverse effects of a halt of perpetual economic growth on the livelihoods of already marginalized and vulnerable communities and the general justice of a degrowth transition. This paper analyses to what extent Environmental Justice theory (EJ) could compensate for this deficit and thus contribute to a more comprehensive and inclusive understanding of justice in the degrowth concept. To do so, the paper firstly establishes gaps across central pillars of degrowth reasoning with regards to a just transition. It discusses evidence that degrowth seeks global socio-ecological justice on distributive grounds and with respect to recognition but falls short in conceptualizing the role that structural power systems (both on micro and macro level) as well as institutional governance mechanisms play in advancing a globally just degrowth transition. The second section of the analysis highlights those concepts within critical EJ theory that, based on the gaps identified, could enable a more extensive understanding of the necessary parameters for a just degrowth transition, namely in the areas of recognition, decoloniality, and theory of the state.
Keywords: F54; H10; O44; Q56; Q58; 330; degrowth; socio-ecological crisis; environmental justice; theory of the state